Astenia dérmica regional hereditária equina: diagnóstico, ocorrência no Brasil e caracterização clinica - Badial, Peres Ramos [UNESP] (2013)
The present study was conducted to characterize the dermatological, ophthalmological, and morphological findings from horses affected with Hereditary Equine Regional Dermal Asthenia (HERDA) and to standardize a High Resolution Melting (HRM) genotyping assay to determine the frequency of carriers. The evaluations and HRM standardization were performed in five affected (AG) and five non-affected (CG) horses. Additionally, five heterozygous (HG) horses were used to HRM standardization. The frequency of carriers was determined in 690 horses. Several skin regions of both groups were measured with a cutimeter Skin biopsies were submitted to histopathological and ultrastructural evaluations. Histopathological evaluation was performed by two pathologists. Ophthalmology included, besides the routine evaluations, corneal diameters measurement, pachymetry, and biometry. HRM was validated using purified DNA from blood samples of the AG, CG, HG and 690 horses. Skin thickness decrease was observed in the AG. Histopathological sensitivity and specificity to diagnose HERDA was dependent on the evaluator and region, respectively. HERDA horses exhibited decreased corneal thickness and increased corneal curvature and corneal diameters. The HRM assay resulted in high accuracy and precision. The estimated carrier frequency was 4.7%. Despite of the regional pattern of the dermatological signs, the decrease of skin thickness from HERDA horses is not regional. Skin samples of the neck, croup or back are recommended to diagnose HERDA. The relevance of the ocular findings should be further investigated. The standardized HRM assay will be useful in the management of breeding programs to minimize the occurrence of this disease